Tracing the development of cognitive variables, regardless kinesthetic sense to learn and retain some kind of Olympic swimming - Adel, Omar; Latif, Maisa (Journal of Physical Education, 2010)
The effect of some develop kinesthetic variables on learning and retaining some swimming styles. This study aims to recognizing the effect of some develop kinesthetic perception variables on learning various swimming styles .The researcher has used the experimental method through conducting a pre-test and a post test for three experimental groups and three control groups. A premeditated homogeneous sample was chosen . it consists of 30 adults who study physical education at Baghdad university. this sample was divided in to 6 groups 5 adults for each group the six groups where pre-tested. then the proposed training kinesthetic perception program was carried out for a period of 8 weeks, with a frequency of 1 hour training ,3 days a week .The t-test was used for identical pairs to test the differences in the variables of the study in pre-test and post test. The result showed significant differences between the pre- test and post –test on the study variables in favor of the pre-test to the experimental groups with (Kinesthetic perception),results of control groups showed significant differences between pre-test and post-test on the study variables to the post-test.The result of both experimental and controlled groups showed significant differences between both of post-test on the study variables and skill performance and retaining to experimental groups with kinesthetic perception.The study there for recommends to use kinesthetic perception programs to learn various swimming styles